A review of high‐mountain acidophilous vegetation in the Iberian Peninsula. Issue 3 (12th June 2017) - Gavilán, Rosario G.; Vilches, Beatriz; Font, Xavier; Jiménez‐Alfaro, Borja
Abstract: Aims: We study the high‐mountain grasslands growing on siliceous substrata of the Iberian Peninsula to determine floristic patterns and affinities that best define the structure and phytosociological classification of this vegetation. Location: Cantabrian Range, Sierra Nevada, Sistema Central, Sistema Ibérico and the Pyrenees. Methods: We analysed 1484 relevés representing 25 phytosociological associations of high‐mountain grasslands on siliceous substrata previously described in the study area. A first classification using noise clustering produced a large noise group containing over 50% of the relevés. We then carried out a DCA to check the relative position of the noise group components with respect to the whole pool, and a K ‐means combined with species indicator analysis to obtain a more precise delimitation of clusters through their representative species. Results: We considered 17 groups as the optimum number of clusters when considering K ‐means and the corresponding indicator species. Pyrenean alpine vegetation separated first, showing a homogeneous pattern with a set of diagnostic taxa organized around two groups that coincide with one European class ( Juncetea trifidi ) and two alliances: Festucion eskiae in chionophilous environments and Festucion supinae in chionophobous habitats. The rest of the data correspond to the Iberian class Festucetea indigestae, recognized in three alliances corresponding to three territories: the Cantabrian Range, Central Iberian Peninsula (Sistema Central and Sistema Ibérico) and Sierra Nevada. Four groups were extracted from the Cantabrian Range, which correspond to temperate (two groups) and Mediterranean (two groups) plant communities included in Teesdaliopsio‐Luzulion . Two groups from Sierra Nevada ‐ one oro‐ ( Thymion serpylloidis ) and another cryoromediterranean ( Ptilotrichion purpurei ) ‐ were separated later on. Some relationships were found between the oromediterranean communities in the Central Mountains (Sierra de Guadarrama) and Sierra Nevada. This highlights the mediterranean character of this central Iberian mountain, compared to the rest of the central ranges (four groups representing cryoromediterranean vegetation) that were independently separated by the analysis and have a more submediterranean character. All are included in Jasionion carpetanae . Conclusions: The Pyrenees and the Cantabrian Range show relationships in high‐mountain vegetation but also differences since the Cantabrian Range has a major influence of Mediterranean taxa in their plant communities. Central Iberian mountains showed relationships with the other Mediterranean mountains through the presence of species of the Festuca indigesta gr. and other endemic taxa. The particular pattern of Sierra Nevada – very patchy and with lower cover values – hindered the separation of groups, but two groups were finally detected in the analysis based on the altitudinal gradient. Abstract : The main patterns on the siliceous alpine vegetation of the Iberian Peninsula are highlighted in terms of floristic composition and altitude using K ‐means in combination with species indicators. They showed the most consistent groups that differentiated all Iberian. Differences and relationships between Temperate (Pyrenees and Cantabrian Range) and Mediterranean ranges (Sistema Ibérico, Sistema Central, and Sierra Nevada) are shown in this paper.